PERAN KETELADANAN GURU MADRASAH IBTIDAIYAH DALAM MEMBENTUK KARAKTER PESERTA DIDIK - Munfa’ati, Kusnul (Journal Of Islamic Elementary School (JIES), 2018)
Character is the quality or strength of mental or moral, morality or character of the individual who is a special personality that becomes the motivator and activator, and differentiate with other individuals. Character can be established through education, because education is the most effective way to awaken the individual in his humanity. Teachers have a very big role in education, especially in the formation of the character of learners. There are 18 basic character values that should be developed for learners: religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, spirit of nationality, love of the homeland, appreciate achievement, communicative, Love peace, love to read, caring environment, sociality and responsible. Teachers have five roles in developing the character of learners, namely as conservator, innovator, transmissist, transformer and organizer.